The Complex Relationships Between Crime, Insecurity and Poverty in Nigeria: Unpacking the State Failure Nexus - Uduo, Thomas Achu; Ofu, Obaji-Akpet Immaculata (New Ideas Concerning Arts and Social Studies Vol. 3, 2025)
Nigeria, frequently referred to as the Giant of Africa due to its vast population and significant economic potential, presents a complex paradox of wealth and poverty. Despite being one of the world’s largest oil producers, Nigeria is plagued by severe challenges such as organised crime, persistent insecurity, and widespread poverty. This study presents a systematic investigation into the intricate interplay between organised crime, insecurity, and poverty in Nigeria, utilising the State Failure Theory as its theoretical groundwork. By drawing on qualitative insights from field research and expert interviews, the research delineates the complex dynamics within this nexus and its profound implications for human security, development, and global stability. Forty comprehensive interviews were conducted with key informants, comprising community members, law enforcement officials, policymakers, and specialists in security. Six focus group discussions were conducted with stakeholders, encompassing youth groups, women’s organisations, and local business owners. This study highlights that the failure of the Nigerian state has fostered an environment permissive to organised criminal activities, which, in turn, exacerbate insecurity and deepen poverty. Key drivers identified in this nexus include corruption, political instability, economic inequality, and institutional weaknesses. The study also highlights the severe impacts on human security, manifesting as widespread violence, displacement, human rights abuses, and socio-economic exclusion. By exploring the intricate relationships among organised crime, insecurity and poverty in Nigeria, this study elucidates the dire consequences of state failure and stresses the necessity for collective action to address this global challenge. The study recommends targeted interventions to strengthen governance and security frameworks, bolster the rule of law, promote sustainable development, and enhance international cooperation to mitigate the global repercussions of state failure.